Dermal Tumors: The Basics - Smoller, Bruce R.; Hiatt, Kim M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Dermal Tumors: The Basics serves as an effective and efficient handbook for the student of dermatopathology, and as a practical bench reference for the practicing diagnostician who desires rapid access to criteria that are useful in differentiating histologically similar entities. The chapters consist of essential bullet points arranged in organized outlines allowing for easy access and direct comparison between entities. The elaborate pictorial documentation will also enable the book to serve as an atlas of the most common dermatologic disorders.
Cutaneous lymphomas -- Vascular Tumors -- Histiocytic Proliferations -- Fibrohistiocytic Proliferations -- Tumors of Fat -- Metastasis -- Further Readings.
Keywords: Medicine; Dermatology; Pathology; Medicine & Public Health; Pathology; Dermatology; Electronic books